Effect of hydration on properties of glucose using explicit and implicit solvent models - Nguyen, Mai Ngoc Thi; Mai, Hanh Hong; Nguyen , Duy Huy (Communications in Physics, 2026)
The interplay between carbohydrates and water molecules is fundamental to understanding the intricate metabolic processes in biological systems. This study examines the structural and electronic properties of hydrated β-glucose, G(H_2O)_n, where 0 ≤ n ≤ 15, using the explicit and implicit solvent models. Explicit (implicit) model reveals that the average length of the H-bond reaches a minimum of 1.76 (1.79) Å when the hydration shell is filled with nine water molecules. Stepwise hydration energies remain negative for all of n, indicating a thermodynamically favorable hydration process. However, the inconsistency between the two models when n is either small (n ≤ 3) or large (n ≥ 13) emphasizes the need for careful selection of the solvent model. For the two models, the trend in HOMO energies is an increase up to n=10 and then a decrease. The energy gap between the highest occupied and lowest unoccupied molecular orbitals is highly sensitive to n for the explicit model. In contrast, it is less sensitive in the implicit model for n ≥ 6. These findings highlight the explicit inclusion of water molecules even when an implicit model is utilized.